Impact of root canal preparation size and taper on coronal-apical micro-leakage using glucose penetration method - Tabrizizadeh, Mehdi (J Clin Exp Dent, 2014)
Objectives: The purpose of this in vitro study was to assess the effect of root canal preparation size and taper on the amounts of glucose penetration. Material and Methods: For conducting this experimental study, eighty mandibular premolars with single straight canals were divided randomly into 2 experimental groups of 30 samples each and 2 control groups. Using K-files and the balance force technique, canals in group 1 were prepared apically to size 25 and coronally to size 2 Peesoreamer. Group 2 were instrumented apically and coronally to size 40 and size 6 Peesoreamer, respectively. Rotary instrumentation was accomplished in group 1; using size 25 and .04 tapered and in group 2, size 35 and .06 tapered Flex Master files. Canals were then obturated by lateral compaction of cold gutta-percha. Glucose penetration through root canal fillings was measured at 1, 8, 15, 22 and 30 days. Data were recorded as mmol/L and statistically analyzed with Mann-Whitney U test (P value=. 05). Results: In comparison to group 1, group 2 showed significant glucose leakage during the experimental period (P value < .0001). Also, in each experimental group, the amount of micro-leakage was significantly increased at the end of the study. Conclusions: Under the condition of this study, the amounts of micro-leakage through root canal fillings are directly related to the size and taper of root canal preparation and reducing the preparation size may lead to less micro-leakage. Key words:Dental leakage, root canal preparation, endodontics.